Fertility resilience varies by socioeconomic status and sex : Historical trends in childlessness across 150 years - Salonen, Milla; Lahdenperä, Mirkka; Rotkirch, Anna; Lummaa, Virpi (Cell Press, 2025)
Fertility dynamics are key drivers of demographic change in a population. Fertility resilience is likely to vary by socioeconomic class, yet little investigated. Using a unique dataset tracking the reproduction of family lineages for 150 years, we explored childlessness by socioeconomic status and sex during the demographic transition and recurring societal and economic disturbances in Finland. Lifetime childlessness doubled from the 1800 birth cohort to the 1945–1949 cohort. Higher socioeconomic status (SES) indicated higher lifetime likelihood to reproduce. The fluctuations in childlessness over time appeared to be driven by the low socioeconomic group, showing low fertility resilience. In contrast, a steady increase was seen in high and moderate SES. Our findings suggest that the family formation of lower socioeconomic groups suffers the most during crises and does not necessarily recuperate. Preventing inequalities in family formation and reproduction should be recognized as a key challenge for population resilience to crises.